Crescimento radicular e aéreo de cultivares de arroz de terras altas em função da calagem - Crusciol, Carlos Alexandre Costa [UNESP] (2012)
This work aimed to evaluate root growth, shoot development and nutrient absorption efficiency by rice cultivars Caiapó and Maravilha as affected by lime application. The experiment was carried out in a greenhouse, with treatments set up by Caiapó and Maravilha cultivars in combination with the base saturation (V%) of 10%, 40% and 70%. The experiment was in a randomized complete block design, with four replications. The number of tillers, root length, root dry matter, leaves and stems, leaf content and macronutrients absorption efficiency were evaluated. Comparing cultivars, Maravilha cultivar presented higher root dry weight, root length, number of stems, dry matter of stems and shoot than Caiapó cultivar, as well as accumulated more nutrients in the shoots. On the other hand, nutrient contents were higher in the cultivar Caiapó compared to Maravilha. Maravilha cultivar shows greater root and shoot growth while Caiapó shows higher nutrient absorption efficiency from the soil. The base saturation of 40% is the most effective for both cultivars.